OFFICIAL STATISTICS UNTUK PEMODELAN INDEKS PENDIDIKAN MELALUI ANALISIS REGRESI DATA PANEL - Meicheil Yohansa (Politeknik Statistika STIS, 2020)
Indonesia as a developing country is doing a lot of various development efforts in many sectors to raise the indices that used to measure a country into a developed country. Not without results, lately, Indonesia is considered as one of the countries that have a stable economy amid conditions of global economic uncertainty. However, the size of a developed country is not only measured through economic conditions but also includes the health and education sectors. This is sometimes seen as a dilemma for the government. On the one hand, the government is aggressively in the distribution of income through infrastructure development. On the other hand, matters relating to people's welfare tend not to be a priority. For example in the education sector which is one of the pillars of the country's development. The highest education index was achieved by DKI Jakarta province as the nation's capital. While inequality is very visible for other regions, even for areas that are still neighbors to DKI Jakarta. In West Java for example. Some areas in West Java are still close to DKI Jakarta, such as Bekasi, Depok, and Bogor. But in fact, the education index in West Java still lags far enough with DKI Jakarta. For this reason, this study aims to compare the factors that influence the education index in West Java, which is divided into cities and districts using panel data regression analysis. The explanatory variables used are the poverty severity index, the number of poor population, population growth rate, and life expectancy respectively for 2011 to 2018. The results show a fixed influence model with a time effect is the best model to describe the education index in urban and district areas with R2 respectively 93.2% and 37.9%.